Correlation Between Acute Dengue Severity and Persistent Post-Dengue Symptoms among Adult Patients: A Prospective Observational Cohort Study in a Tertiary-Care Hospital in Bangladesh - Abu Saleh Mohammed Sirajum Munir; Abhizit Pandit; Md. Noman Hossain; Mohammed Jahedul Islam (SAS Journal of Medicine, 2026)
Background: Dengue infection is a major cause of acute febrile illness and may be followed by persistent symptoms that affect recovery and daily functioning. This study aimed to assess the correlation between acute dengue severity and persistent post-dengue symptoms among adult patients. Methods: This prospective observational cohort study was conducted in the Department of Medicine, Mugda Medical College, from July 2025 to December 2025. In total 90 adult patients with laboratory-confirmed dengue infection. Participants were enrolled during the acute phase and categorized as having dengue without warning signs, dengue with warning signs, or severe dengue according to standard clinical criteria. Socio-demographic, clinical, laboratory and hospitalization data were recorded and patients were followed to assess persistent post-dengue symptoms. Data were analyzed using SPSS version 25 and associations were assessed using appropriate statistical tests. Results: Dengue with warning signs was the most common severity category (42.2%), followed by dengue without warning signs (37.8%) and severe dengue (20.0%). Persistent post-dengue symptoms were observed in 65.6% of participants, with fatigue (43.3%), generalized weakness (37.8%), myalgia (30.0%) and arthralgia (26.7%) being the most frequent complaints. Persistent symptoms increased with acute disease severity, occurring in 38.2% of patients with dengue without warning signs, 71.1% with warning signs and 94.4% with severe dengue. The association between acute dengue severity and persistent post-dengue symptoms was statistically significant (p